Analisis Kelayakan Buku Teks Bahasa Indonesia untuk Siswa Kelas VIII Sekolah Menengah Pertama - Abdullah S Abdullah S; Susilo Susilo; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
The purpose of this study was to determine and describe the quality/feasibility of the textbook “Mahir Berbahasa Indonesia” published by Erlangga Publisher and “Bahasa Indonesia Kelas VIII SMP/MTs Edisi Kurikulum 2013 Revisi” published by Yudhistira Publisher. It is a content analysis research that describes objectively, systematically, and clearly communicates from the VIII Indonesian Language and Literature Book. Research technique to objectively, systematically and quantitatively describe clear communication content. Based on the analysis and findings of the feasibility of books using the BNSP standard, the book “Mahir Berbahasa Indonesia” for class VIII SMP/MTs published by Erlangga Publisher is considered feasible with a percentage of 75%. In comparison, the book “Bahasa Indonesia Kelas VIII SMP/MTs Edisi Kurikulum 2013 Revisi” issued by Yudhistira Publisher is considered feasible with a percentage of 71.60%.